Chronic alcohol consumption and its effect on nodes of frontocerebellar and limbic circuitry: Comparison of effects in France and the United States. Issue 9 (17th March 2014) - Le Berre, Anne‐Pascale; Pitel, Anne‐Lise; Chanraud, Sandra; Beaunieux, Hélène; Eustache, Francis; Martinot, Jean‐Luc; Reynaud, Michel; Martelli, Catherine; Rohlfing, Torsten; Sullivan, Edith V.; Pfefferbaum, Adolf
Abstract Alcohol use disorders present a significant public health problem in France and the United States (U.S.), but whether the untoward effect of alcohol on the brain results in similar damage in both countries remains unknown. Accordingly, we conducted a retrospective collaborative investigation between two French sites (Caen and Orsay) and a U.S. laboratory (SRI/Stanford University) with T1‐weighted, structural MRI data collected on a common imaging platform (1.5T, General Electric) on 288 normal controls (NC), 165 uncomplicated alcoholics (ALC), and 26 patients with alcoholic Korsakoff's syndrome (KS) diagnosed at all sites with a common interview instrument. Data from the two countries were pooled, then preprocessed and analyzed together at the U.S. site using atlas‐based parcellation. National differences indicated that thalamic volumes were smaller in ALC in France than the U.S. despite similar alcohol consumption levels in both countries. By contrast, volumes of the hippocampus, amygdala, and cerebellar vermis were smaller in KS in the U.S. than France. Estimated amount of alcohol consumed over a lifetime, duration of alcoholism, and length of sobriety were significant predictors of selective regional brain volumes in France and in the U.S. The common analysis of MRI data enabled identification of discrepancies in brain volume deficits in France and the U.S. that may reflect fundamental differences in the consequences of alcoholism on brain structure between the two countries, possibly related to genetic or environmental differences. Hum Brain Mapp 35:4635–4653, 2014. © 2014 Wiley Periodicals, Inc.